Assessing academic impact through a bibliometrics analysis: Gastroesophageal reflux disease in the context of obesity treatment and bariatric surgery - Akbayan Imanbayeva; Bazylbek Zhakiev; Asset Yelemessov; Kairat Adaibayev; Kymbat Tussupkaliyeva; Dulat Turebayev; Saltanat Urazova; Laura Mamesheva; Alireza Afshar (SAGE Open Medicine)
Aims: The global rise in obesity rates has led to increased use of bariatric surgery, which can potentially exacerbate or induce gastroesophageal reflux disease. This study aimed to assess the academic impact and trends in research on gastroesophageal reflux disease in the context of obesity treatment and bariatric surgery through a comprehensive bibliometric analysis. Materials and methods: A bibliometric analysis was conducted using data from Web of Science and Scopus databases, covering publications from 1993 to 2024. The study utilized the Bibliometrix R package to analyze publication trends, collaborative networks, and research topics. Results: The analysis encompassed 257 documents from 82 sources, with 6192 total citations and an 8.2% annual growth rate in publications. The United States emerged as the leading contributor with 90 publications. Key research topics included bariatric surgery, sleeve gastrectomy, and gastroesophageal reflux disease, with increasing focus on complications and revisional bariatric surgery in recent years. Two main research clusters were identified: one focusing on general health aspects and demographics, and another on specialized bariatric procedures and outcomes. However, the analysis is constrained by its reliance on data from only two bibliographic databases, which may not encompass all pertinent studies, and by a geographic bias toward high-income countries. Moreover, our deep literature reviews highlighted that obesity is a known risk factor for gastroesophageal reflux disease, and while Roux-en-Y gastric bypass often reduces gastroesophageal reflux disease symptoms, sleeve gastrectomy may exacerbate or cause de novo gastroesophageal reflux disease postoperatively. Conclusions: This bibliometric study reveals a significant increase in research activity on gastroesophageal reflux disease in relation to obesity treatment and bariatric surgery, particularly since 2017. The findings highlight the growing importance of this field and the need for continued international research efforts to optimize surgical protocols and improve patient outcomes.